Republic of Mozambique : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This report on the Observance of Standards and Codes data module provides a review of Mozambique's data dissemination practices against the IMF's General Data Dissemination System (GDDS) by in-depth assessment of the quality of the national accounts, consumer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that with the exception of monetary statistics, there are limitations in the coverage of all core comprehensive frameworks and indicators recommended in the GDDS. With respect to periodicity and timeliness, most GDDS recommendations have been met.